Molecular Detection and Characterization of Mycoplasma pneumoniae Among Patients Hospitalized With Community-Acquired Pneumonia in the United States. (16th July 2015) - Diaz, Maureen H.; Benitez, Alvaro J.; Cross, Kristen E.; Hicks, Lauri A.; Kutty, Preeta; Bramley, Anna M.; Chappell, James D.; Hymas, Weston; Patel, Anami; Qi, Chao; Williams, Derek J.; Arnold, Sandra R.; et al.
Abstract : We report molecular characteristics of M. pneumoniae in respiratory specimens from children and adults hospitalized with CAP. The P1 type 1 genotype and MLVA type 4/5/7/2 predominated, but proportions of types differed between children and adults. Macrolide resistance was rare. Abstract: Background.   Mycoplasma pneumoniae is a common cause of community-acquired pneumonia (CAP). The molecular characteristics of M pneumoniae detected in patients hospitalized with CAP in the United States are poorly described. Methods.  We performed molecular characterization of M pneumoniae in nasopharyngeal/oropharyngeal swabs from children and adults hospitalized with CAP in the Centers for Disease Control and Prevention Etiology of Pneumonia in the Community (EPIC) study, including P1 typing, multilocus variable-number tandem-repeat analysis (MLVA), and macrolide susceptibility genotyping. Results.  Of 216 M pneumoniae polymerase chain reaction-positive specimens, 40 (18.5%) were obtained from adults and 176 (81.5%) from children. P1 type distribution differed between adults (64% type 1 and 36% type 2) and children (84% type 1, 13% type 2, and 3% variant) ( P < .05) and among sites ( P < .01). Significant differences in the proportions of MLVA types 4/5/7/2 and 3/5/6/2 were also observed by age group ( P < .01) and site ( P < .01). A macrolide-resistant genotype was ide.jpegied in 7 (3.5%) specimens, 5 of which were from patients who had recently received macrolide therapy. No significant differences in clinical characteristics were ide.jpegied among patients with various strain types or between macrolide-resistant and -sensitive M pneumoniae infections. Conclusions.  The P1 type 1 genotype and MLVA type 4/5/7/2 predominated, but there were differences between children and adults and among sites. Macrolide resistance was rare. Differences in strain types did not appear to be associated with differences in clinical outcomes. Whole genome sequencing of M pneumoniae may help ide.jpegy better ways to characterize strains.